2021
DOI: 10.1155/2021/9940645
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of Acupuncture Based on Smart Medical Care for Post-Stroke Hemiplegic Shoulder Pain and Upper Limb Motor Function

Abstract: As a new stage in the development of medicine and health, smart medicine has attracted attention from all parties in recent years. Especially, under the impetus of the Internet, due to the development of new technologies, smart medical care has made considerable progress, and it has also brought us new challenges. The concept, hypothesis, and design of intelligent medical care are analyzed, and the design objects and design principles of intelligent medical care are highlighted. In Africa, 79 patients with sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%